KERAGAMAN JENIS TANAMAN PADA SISTEM AGROFORESTRI PEKARANGAN DI DESA WAREMBUNGAN - Yaromi Yoman; Euis F.S. Pangemanan; Semuel P. Ratag (Universitas Sam Ratulangi, 2017)
ABSTRACT Â The traditional agroforestry homegarden in the village when judging from the vegetation composition it have interesting characteristics. Village homegarden ecosystems have a very diverse ecosystem service function and play an important role in the lives of rural communities. The purpose of this research is to know the diversity of plant species in agroforestry homegarden in Warembungan Village. The method used in this research is the interview method by using questionnaires as a means of collecting primary data and secondary data and direct field observation Based on the results of research in Warembungan Village, Pineleng District found 53 species of homegarden plants. The diversity of plant species consists of 24 families. The diversity of plant species consists of 24 families. Most of the homegarden plants are spices with 279 plants, 257 fruits plants, and 180 vegetables plants. Meanwhile, 159 tuber plants 90 ornamental plants, and 82 timber plants.Total individu 1,047 plants and the location of front, side and back of respondent's house. Â Keywords :Diversity of plant, types, agroforestry, homegarden